2022
DOI: 10.1155/2022/9180696
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Risk Factors for Postoperative Lower Extremity Deep Venous Thrombosis and its Treatment and Nursing

Abstract: Objective. To explore the risk factors of lower extremity deep venous thrombosis (LEDVT) after surgery and discuss the treatment and nursing countermeasures. Methods. A retrospective analysis was conducted on 268 surgical patients admitted between July to December 2021. The factors associated with LEDVT were analyzed using the Logistic regression model. Further, LEDVT patients were assigned to a research group treated with targeted nursing to prevent LEDVT and a control group that used routine care. Coagulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The criteria of (age, APTT, D-dimer and history of hypertension) was applied to the entire patient population of this study to determine a reference predictive model ( Han et al, 2021 ; Liu & Peng, 2022 ; Liu et al, 2021 ; Liu et al, 2006 ). Cohen’s kappa coefficient ( κ ) was 0.375 ( P < 0.001) when comparing the prediction of low-risk group between the criteria from other studies and the predictive model suggested by this study were compared.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The criteria of (age, APTT, D-dimer and history of hypertension) was applied to the entire patient population of this study to determine a reference predictive model ( Han et al, 2021 ; Liu & Peng, 2022 ; Liu et al, 2021 ; Liu et al, 2006 ). Cohen’s kappa coefficient ( κ ) was 0.375 ( P < 0.001) when comparing the prediction of low-risk group between the criteria from other studies and the predictive model suggested by this study were compared.…”
Section: Resultsmentioning
confidence: 99%
“…The criterion value for LEDVT prediction was determined through receiver operating characteristic (ROC) curve analysis. The criteria from other studies (age, APTT, D-dimer and history of hypertension) were applied to the entire patient population of this study as to determine a reference predictive model ( Han et al, 2021 ; Liu & Peng, 2022 ; Liu et al, 2021 ; Liu et al, 2006 ). This is followed by Cohen’s kappa coefficient ( κ ) analysis to compare predictive value between the criteria from other studies and the predictive model suggested by this study ( Morrison et al, 2013 ).…”
Section: Methodsmentioning
confidence: 99%
“…The general comfort questionnaire (GCQ), developed by Kolcaba et al based on the study of comfort theory [6], is a widely cited tool for measuring comfort. It has been translated and tested for reliability and validity by domestic scholars and is now widely used in the Chinese language [7][8][9]. The content of the comfort scale comprises four dimensions: physical, psychological, socio-cultural, and environmental, encompassing a total of 30 questions.…”
Section: Introductionmentioning
confidence: 99%